Perspiria boucheri sp. nov. (Nematoda, Desmodorida) from the East China Sea - Sun, Jing; Zhai, Hongxiu; Huang, Yong (Zootaxa, 2019)
A new free-living marine nematode species from marine sediments in the East China Sea, is described here as Perspiria boucheri sp. nov. The new species is characterized by amphideal fovea surrounded partially by body annulations; four cephalic setae stout; conical buccal cavity with a minute dorsal tooth and two ventrosublateral teeth; pharynx with a pyriform terminal bulb; tail elongated, conical with 3/4 posterior cylindrical portion which having distinct coarse annulations; spicules strongly curved with narrow ventral velum, handle-shaped proximally; gubernaculum canoe-shaped, without apophysis. The new species differs from the most similar species Perspiria striaticaudata (Timm, 1962) by strongly curved spicules with handle-shaped proximal end, gubernaculum without dorsal apophysis and relatively shorter tail. Updated key to all species of Perspiria is provided.